A modular and concise approach to MIDA acylboronates via chemoselective oxidation of unsymmetrical geminal diborylalkanes: unlocking access to a novel class of acylborons. Issue 17 (2nd April 2019) - Lin, Shengjia; Wang, Lucia; Aminoleslami, Negin; Lao, Yanting; Yagel, Chelsea; Sharma, Abhishek
Abstract : Novel and mild synthesis of MIDA acylboronates including a novel class of acylborons and first chemoselective oxidation of geminal diborylalkanes. Abstract : Acylboronates represent a very intriguing and rare class of organoboronates. Synthesis of these compounds from readily available substrates under mild conditions and access to novel classes of acylborons has been challenging. We report a novel and concise route to various MIDA acylboronates from terminal alkynes/alkenes or vinyl boronic esters using unsymmetrical geminal diborylalkanes as key intermediates. The high modularity and mild conditions of this strategy allowed a facile access to acylboronates possessing aliphatic, aromatic as well as the rarer heteroaromatic, alkynyl and α, β-unsaturated scaffolds. To the best of our knowledge, this is the first report of chemoselective oxidation of geminal diborons as well as synthesis of an α, β-unsaturated acylboronate.